2015
DOI: 10.1073/pnas.1516814112
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the reliability of eyewitness identifications from police lineups

Abstract: Laboratory-based mock crime studies have often been interpreted to mean that (i) eyewitness confidence in an identification made from a lineup is a weak indicator of accuracy and (ii) sequential lineups are diagnostically superior to traditional simultaneous lineups. Largely as a result, juries are increasingly encouraged to disregard eyewitness confidence, and up to 30% of law enforcement agencies in the United States have adopted the sequential procedure. We conducted a field study of actual eyewitnesses who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
192
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(204 citation statements)
references
References 28 publications
11
192
0
1
Order By: Relevance
“…The results revealed no significant relationship between the type of line-up procedure undertaken and identification accuracy for either simultaneous or sequential line-ups; participants in the sequential line-up condition were no more accurate in their identifications than those in the simultaneous line-up condition. Such findings are consistent with previous literature, which suggested that, when examining procedural difference effects between simultaneous and sequential techniques, utilising genuine or more realistic line-up procedures to those used within real police identifications, rates of accurate and inaccurate identifications remain similar (Wells et al, 2015;Wixted et al, 2016). Corresponding with Malpass et al (2009) and Meissner et al (2005), the present results suggest that when removing the memory component in line with the mock witness paradigm, sequential line-up procedures provide little superior effects upon eyewitness identifications than those obtained within traditional simultaneous line-ups.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The results revealed no significant relationship between the type of line-up procedure undertaken and identification accuracy for either simultaneous or sequential line-ups; participants in the sequential line-up condition were no more accurate in their identifications than those in the simultaneous line-up condition. Such findings are consistent with previous literature, which suggested that, when examining procedural difference effects between simultaneous and sequential techniques, utilising genuine or more realistic line-up procedures to those used within real police identifications, rates of accurate and inaccurate identifications remain similar (Wells et al, 2015;Wixted et al, 2016). Corresponding with Malpass et al (2009) and Meissner et al (2005), the present results suggest that when removing the memory component in line with the mock witness paradigm, sequential line-up procedures provide little superior effects upon eyewitness identifications than those obtained within traditional simultaneous line-ups.…”
Section: Discussionsupporting
confidence: 90%
“…Alongside acknowledging the need for inclusion of personality assessments, the need to replicate the present findings within a more formal policing environment is required. Despite using an array of images derived from a genuine police investigation alongside an attempt to simulate the layout of a police interview room, the conditions under which participants observed photographs were more akin to laboratory settings than a police station -a factor which some research has shown to impact the strength and direction of results (Wixted et al, 2016). Furthermore, participants were not actual witnesses to the crime in which they were asked to make line-up identifications about and based selections wholly upon standardised descriptions provided to them.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies using a more sophisticated statistical approach based on receiver operating characteristics indicate, however, that the primary effect of the sequential procedure is the elicitation of more conservative responses on the part of the eyewitness: witnesses simply make fewer lineup picks (17). Furthermore, several reports now suggest that witnesses are better able to optimize sensitivity to their memories-that is, they manifest better discriminability-when simultaneous lineups are used (17,(22)(23)(24). Future research may identify how variations of these or other lineup procedures can further improve performance, but the NAS committee on eyewitness identification concluded that there was not sufficient evidence to warrant a change from the traditional simultaneous procedure.…”
Section: Variables That Influence Eyewitness Performancementioning
confidence: 99%